Aesthetic values in home and consumer studies – investigating the secret ingredient in food education - Berg, Gita; Lundqvist, Eva; Sydner, Ylva Mattsson (Frontiers in Education, 2023)
Food is a part of everyday life, and formal food education is included in compulsory education in many countries, for example through the subject Home and Consumer Studies (HCS). While food education is often underpinned by public health concerns such as preventing non-communicable diseases and promoting cooking skills, there has been little focus on aesthetic aspects of teaching and learning about food. This study therefore aims to gain understanding of aesthetic values as a part of HCS food educational practices. Aesthetic values are here regarded as socially and culturally shared, and related to notions of pleasure and taste. As this study uses a pragmatist approach, aesthetic values are seen as constituted in encounters, encompassing experiencing individual(s), artifacts, and context. By thematically analyzing empirical data from an exploratory case study, including classroom observations, student focus groups, and teacher interviews, we show how values are constituted as culinary, production, and bodily aesthetics. Culinary aesthetics involved cooking processes, cooking skills, and presentation of food and meals. Production aesthetics involved foods' origin and degree of pre-processing, whereas bodily aesthetics related to bodily consequences of eating. Aesthetic values were vital features of the educational practices studied and played a key role in bringing the practices forward. They also indicated what counted as valid, or desired, outcomes and thereby steered events in certain directions. The study highlights the significance of aesthetic values and argues in favor of acknowledging aesthetics in planning, undertaking, and evaluating HCS food education.